2011
DOI: 10.1111/j.1365-2958.2010.07526.x
|View full text |Cite
|
Sign up to set email alerts
|

A phage‐encoded inhibitor of Escherichia coli DNA replication targets the DNA polymerase clamp loader

Abstract: SummaryColiphage N4 infection leads to shut-off of host DNA replication without inhibition of host transcription or translation. We report the identification and characterization of gp8, the N4 gene product responsible for this phenotype. N4 gp8 is an Escherichia coli bacteriostatic inhibitor that colocalizes with the E. coli replisome in a replication-dependent manner. Gp8 was purified and observed to cross-link to complexes containing the replicative DNA polymerase, DNAP III, in vivo. Purified gp8 inhibits D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…DNA replication is often a target of early phage proteins (Datta et al, 2005; Yano and Rothman-Denes, 2011). However, expression of genes involved in replication (Xu et al, 2010) was not significantly altered in the presence of gp67 in vivo (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…DNA replication is often a target of early phage proteins (Datta et al, 2005; Yano and Rothman-Denes, 2011). However, expression of genes involved in replication (Xu et al, 2010) was not significantly altered in the presence of gp67 in vivo (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Other mechanisms redirect bacterial metabolic pathways to the bacterial virus reproduction cycle. Through “Inhibition of host DNA replication”, viruses prevent host replication and division, thereby improving available dNTPs and metabolic activity for their own replication [50,51]. …”
Section: Resultsmentioning
confidence: 99%
“…We found that M1 blocks host cell DNA replication likely by interacting with SLD5 to disrupt the normal function of the GINS complex. Some bacterial virus can shut off host DNA replication to arrest host growth (Belley et al, 2006;Seco et al, 2013;Yano & Rothman-Denes, 2011). First, knockdown or mutation of SLD5 (△7aa) in cells resulted in delayed cell cycle progress.…”
Section: Discussionmentioning
confidence: 99%
“…Several pieces of evidence support this founding. Bacteriophage N4, for example, is known to shut off host DNA replication, whereas the host genome remains structurally intact (Yano & Rothman-Denes, 2011). It has been reported that SLD5 interacts with Psf1, Psf2, and Psf3 (Choi et al, 2007;Gouge & Christensen, 2010;Joshi et al, 2016;Takayama et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation